Estratégias para conservação da biodiversidade em assentamento rural no baixo São Francisco - Amaral, Luise Andrade (2022)
Forest restoration has great importance as an alternative to mitigate climate change. Therefore, measuring the development status of ecosystems in the process of restoration combined with the dynamics of land use and occupation becomes essential for biodiversity conservation. Thus, this study aimed to analyze existing information on studies of modeling the distribution of species in forest restoration, in addition to identifying and understanding the ecological trajectory of the riparian area of the Borda da Mata Settlement, municipality of Canhoba, lower São Paulo region, Francisco Sergipano, in the process of restoration, has been following, through the interaction of floristic, phytosociological, edaphic and geoenvironmental information. A reforestation project was carried out in 2004 in the permanent preservation area - APP of the Borda da Mata Settlement, located on the right bank of the lower course of the São Francisco River. In that region, strips of land o 30 meters in width, beginning from the edge of the along the regular river bed, in an extension of 5 km, were fenced to carry out the planting of seedlings of forest species native to the region with a spacing of 3 x 3 meters. In 2021, to evaluate the vegetation of this area, 19 plots of 600m2 were installed, where all live arboreal shrubs that presented a circumference at breast height greater than or equal to ten centimeters (CAP ≥ 10 cm) and total height greater than or equal to one meter (HT ≥ 1m) were measured and classified according to the successional and functional group and dispersion syndromes. The horizontal and vertical structures were also characterized, and the floristic diversity was evaluated using the Shannon-Weaver Index (H') and the Pielou equability (J'). For temporal analysis of the landscape, data from the MapBiomas collection for 2004, 2008, 2012, 2016 and 2020 were used. For analysis of chemical attributes, soil samples were collected in three areas within the settlement (reforested riparian forest, agricultural area and legal reserve area) that were analyzed by the Technological Research Institute of the State of Sergipe – ITPS, according to the Embrapa methodology (2009). The floristic composition survey observed the occurrence of 35 species belonging to 32 genera and distributed in 12 botanical families, totaling a richness of 490 individuals. The Fabaceae and Anacardiaceae families represented 71.43% of the total species richness. As for the successional stages, 42.86% of the species are initial secondary ones, with zoochoric dispersion syndrome representing 51.43%. The Shannon-Wiener index (H') was 2.98 nats/ind. and the Pielou Equability (J') was 0.79. The highest values of relative density, absolute frequency and relative frequency were found for Schinus terebinthifolia species. However, the highest importance value index was found for Lonchocarpus sericeus. The riparian area of the study has a medium richness of species but a positive evolution for soil fertility. By the temporal landscape analysis, a decrease in the natural areas of the settlement in comparison with the anthropic areas was observed. Significant restoration influence was observed with an increasing forest establishment in the settlement in 2020, e.g., a gain of 8.55 ha compared to 2004. Regarding soil fertility, the Legal Reserve area was the area that presented the best rates.